Comparison of the Effect of Four Decalcifying Agents Combined with 60°C 3% Sodium Hypochlorite on Smear Layer Removal - Wu, Ligeng; Mu, Ying; Deng, Xiuli; Zhang, Shasha; Zhou, Dongyan (Journal of endodontics, 2012)
The objective of this study was to compare the efficacy on smear layer removal of 4 decalcifying agents: 17% ethylenediaminetetraacetic acid (EDTA), 20% citric acid, BioPure MTAD, and SmearClear. Forty-five single-rooted human teeth were used and prepared up to ProTaper F3. After each instrumentation, 1 mL of 3% NaOCl at 60°C was irrigated for 1 minute. All the samples were randomly divided into 5 groups according to the final irrigants: 17% EDTA, 20% citric acid, BioPure MTAD, SmearClear, and 3% NaOCl (control). The smear layer removal of all groups at the apical, middle, and coronal thirds was observed under the thermal field emission scanning electron microscope. The EDTA group was significantly more effective than the SmearClear and MTAD groups (P < .05). The efficacy of all three thirds in the EDTA, MTAD, and SmearClear groups can be arranged as coronal, middle, and apical thirds (P < .05) from excellent to poor. However, in the citric acid group, the coronal two thirds were significantly better than the apical third (P < .05), and there was no statistical significance between the coronal and middle thirds (P > .05). The 4 decalcifying agents could effectively, but not completely, remove the smear layer, especially in the apical third. The efficacy of 17% EDTA was better than that of MTAD and SmearClear.